EPIDEMIOLOGY OF PREDIABETES AND IT’S DIAGNOSIS AND TREATMENT: A REVIEW - ASHRAF , S; TAHIR , A; SHABBIR , A; AWAIS , M; ALI , A; SHAHZADI , R; ULLAH , S; IMTIAZ , R; HAMEED , S (Biological and Clinical Sciences Research Journal, 2023)
A state of hyperglycemia known as prediabetes is characterized by glycemic indices that are above normal but still below the diabetes threshold. Pre-diabetes remains significantly connected with a yearly conversion rate of 5% to 10% to diabetes, even with differences in the diagnostic criteria among international professional organizations. Observational research suggests a potential link between prediabetes and diabetic sequelae, including small fiber neuropathy, early retinopathy, early nephropathy, and an increased risk of macrovascular disease. Numerous studies showing the value of lifestyle changes in avoiding diabetes have shown a relative risk reduction of 40%–70% in those with prediabetes. Although there is growing evidence that pharmaceutical therapy alternatives other than metformin are beneficial in preventing diabetes in individuals with prediabetes, their use is limited due to adverse effects. The health outcomes of childhood prediabetes have not been the subject of any rigorous evaluations. Pharmacotherapy for prediabetes may have uncertain consequences on a child’s growth and pubertal development. High-risk individuals are advised to undergo secondary intervention with metformin pharmacotherapy; nevertheless, the eventual goal of therapy, the long-term cost-effectiveness of such interventions, and the advantages of early intervention are not well understood. In kids with prediabetes, pharmacotherapy needs to be used carefully. Prediabetes is the term for blood glucose levels that are higher than usual but not entirely above the diabetic threshold. In this at-risk status, diabetes is considered to be highly likely to develop. Even though prediabetes is usually an asymptomatic condition, it is always present before the beginning of diabetes. As hyperglycemia is a continuum, prediabetes cannot be ruled out as a completely benign illness. In this review, we discussed the difficulties in diagnosing prediabetes, the potential adverse health consequences that come with it, the available treatments for prediabetes, and the reasons behind using them.